108 Impact of Health Literacy on Satisfaction Following Inflatable Penile Prosthesis Surgery. Issue 1 (1st April 2022) - Bhalla, R; Furuyama, W; Calvert, J; Ball, M; Dropkin, B; Milam, D; Kaufman, M; Johnsen, N
ABSTRACT: Introduction: Health literacy - the ability to obtain, comprehend, and act on basic medical information - can impact surgical outcomes and patient quality of life (QOL). Urologic prosthetic surgery aims to improve a patient's QOL, therefore patient satisfaction is a fundamental measure of success. Objective: We sought to determine whether health literacy impacts patient satisfaction following inflatable penile prosthesis (IPP) surgery for erectile dysfunction. Methods: We performed a single-institution retrospective study of patients who underwent IPP insertion between January 1st 2016 and July 31st 2020. A patient satisfaction phone questionnaire was administered between October 2020 and January 2021 to measure: (1) overall satisfaction with IPP surgery on a Likert scale and (2) if patients would undergo IPP surgery again. Baseline health literacy was measured using the Brief Health Literacy Screen (BHLS) – a validated 3-item questionnaire. Ordinal logistic regression was used to assess the association between health literacy and patient satisfaction, adjusting for the predetermined covariates of patient age, marital status, preoperative Sexual Health Inventory for Men (SHIM) scores, time from surgery to phone questionnaire, and device functionality. Results: A total of 162 IPP patients met study inclusion criteria. The cohort consisted of primarily Caucasian (81.5%) and married (74.7%) men with a median age of 64.5 years and an interquartile range (IQR) of 57.5-69.5 years. The median (IQR) BHLS score was 15 (13-15) and the median (IQR) time from the index surgery to phone questionnaire administration was 2.41 (1.39-3.98) years. 69.8% of men were either very satisfied or satisfied with their procedure, and 74.1% of men would again undergo IPP surgery. After adjustment for potential confounders, BHLS score was significantly associated with patient satisfaction after IPP surgery (OR 1.31, 95% CI 1.11-1.54; p=0.001) and was positively associated with likelihood of again undergoing IPP surgery (OR 1.53, 95% CI 1.25-1.87; p<0.001) (Table 1). Conclusions: Patients with lower health literacy are less likely to be satisfied following IPP placement. The BHLS score is an important tool that can be used to identify patients who may benefit from increased preoperative counseling and education to further improve patient expectations and QOL following IPP surgery. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Boston Scientific